The Effect of Waste Molasses on the Growth and the Amount of Lipid and Protein of Chlorella vulgaris - Şimşek, Gökçe Kendirlioğlu; Cetin, Ahmet Kadri (Uğur ÇAKILCIOĞLU, 2022)
In recent years, microalgae have become the focus of attention because they are used in different fields (biodiesel, protein extraction, etc.). One disadvantage of microalgae is that their production costs are pretty high. This paper aimed to reduce the cultivation costs of Chlorella vulgaris, which is an important species in terms of protein and lipid content. Molasses solutions at different concentrations were used as media for the cultivation of C. vulgaris. Molasses is a byproduct of the extraction of sucrose from sugar beets. A Jaworski’s medium was used as the control group. C. vulgaris was inoculated into molasses media (0.5 g/L, 1 g/L, 2 g/L, and 4 g/L). Growth and protein, and lipid content were calculated for ten days. C. vulgaris had the highest growth in 4 g/L molasses medium on day five. It had the highest protein content in 2 g/L molasses medium on day five. It had the highest lipid content in 4 g/L molasses medium on day seven. The molasses media promoted the growth and the protein and lipid content of C. vulgaris. The results show that molasses media help significantly reduce microalgae cultivation costs.
Keywords: Structural Biology; Yapısal Biyoloji